GRAMMAR CONTENT KNOWLEDGE OF TAMIL LANGUAGE AMONG SECONDARY SCHOOL TEACHERS - Bavani Arumugam; Alagesan Ambikapathy; Surenthiran Verappan, (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
The study aims to identify the level of knowledge of grammar content among Tamil language teachers at the secondary school level in aspects of phonology, morphology, syntax and morphophonemic. This study uses a quantitative research survey in the form of a descriptive design carried out in Selangor. A total of 160 Tamil language teachers in secondary schools in the state of Selangor were selected as a random sample. Questionnaires were used as instruments in this study. The data obtained were analyzed using SPSS software version 22.0. The findings of the study showed that secondary school Tamil teachers had a moderately high perception of the Tamil grammatical content of Form Four (M = 3.23, SP =.697). The study also found that the level of knowledge of Tamil grammar content was moderately low (M = 2.98, SP =.334) by following phonology (M = 3.26, SP =.560), morphology (M = 3.14, SP =.589), syntax (M = 2.85, SP =.716), and morphophonemic (M = 2.67, SP =.585). The implication obtained through this study is that the Ministry of Education Malaysia (MOE) is proposing to emphasize the importance of aspects of Tamil grammar, namely phonology, morphology, syntax, and morphophonemic. As a result of this, teachers who teach Tamil will be able to realize the importance of mastering the content of Tamil grammar.